2021
DOI: 10.1007/s00170-021-07298-7
|View full text |Cite
|
Sign up to set email alerts
|

Grain flash temperatures in diamond wire sawing of silicon

Abstract: Diamond wire sawing has obtained 90% of the single-crystal silicon–based photovoltaic market, mainly for its high production efficiency, high wafer quality, and low tool wear. The diamond wire wear is strongly influenced by the temperatures in the grain-workpiece contact zone; and yet, research studies on experimental investigations and modeling are currently lacking. In this direction, a temperature model is developed for the evaluation of the flash temperatures at the grain tip with respect to the grain pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The different trends in pressure with increasing cutting speed at 70 and 250 nm/rev feed may be related to the combined effect of thermal softening of the material due to increasing temperature at the cutting zone and material strengthening due to increasing strain rate [12]. Pala et al [15] developed a flash temperature model for diamond wire cutting of silicon. They showed that at nanometric cutting depths, flash temperatures would reach to up to 2500 K.…”
Section: Resultsmentioning
confidence: 99%
“…The different trends in pressure with increasing cutting speed at 70 and 250 nm/rev feed may be related to the combined effect of thermal softening of the material due to increasing temperature at the cutting zone and material strengthening due to increasing strain rate [12]. Pala et al [15] developed a flash temperature model for diamond wire cutting of silicon. They showed that at nanometric cutting depths, flash temperatures would reach to up to 2500 K.…”
Section: Resultsmentioning
confidence: 99%